Sosialisasi UU ITE tentang Bersosial Media dengan Benar dan Bahaya Judi Online - Mukhammad, Udi Noor; Nira, Yulita Ayun; Hartanto, Defri (Muria Jurnal Layanan Masyarakat, 2024)
Social media is media in the form of sites or applications that involve internet-based technology. As social media users increase, there is increasingly widespread misuse of these platforms for crimes that harm themselves and others. The reason is that when using social media we have to be ethical, therefore we are holding outreach at the KWT women's place in Banyu Urip Village. And the dangers of online gambling are becoming more and more common among teenagers and men, many are caught in the trap of online gambling addiction, which can waste their time and money without limits, affecting their financial stability, apart from the financial impact, online slot gambling also can damage social and family relationships. For this reason, we conducted research on this online slot gambling case when teenagers from Banyu Urip Village were hanging out at night in coffee shops and at the patrol post.